The partial differential equation obtained by eliminating a and b from (x − a)^{2} + (y − b)^{2} = z^{z} cot^{2}α is

p^{2} − q^{2} = tan^{2}α

p^{2} + q^{2} = tan^{2}α

p^{2} + q^{2} = cot^{2}α

p^{2} − q^{2} = tanα

Ans: (b)

The partial differential equation obtained by eliminating a and b from x^{2} + y^{2} + (z − a)^{2} = b^{2} is

py = qx

py + qx = 0

px = qy

px + qy = 0

Ans: (a)

The partial differential equation obtained by eliminating a and b from

py = qx

px + qy = 0

Ans: (c)

The partial differential equation obtained by eliminating the arbitrary function ...

With Safari, you learn the way you learn best. Get unlimited access to videos, live online training,
learning paths, books, interactive tutorials, and more.